2020
DOI: 10.2147/jir.s280091
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mangiferin Inhibits Apoptosis and Autophagy Induced by <em>Staphylococcus aureus</em> in RAW264.7 Cells</p>

Abstract: Purpose Staphylococcus aureus ( S. aureus ) is an important bacterial pathogen, which creates infective inflammation to human being and animals. Mangiferin (MG) is one of the natural flavonoids with anti-inflammatory, anti-bacterial, and anti-oxidative properties. However, the anti-apoptosis and anti-autophagy of MG are unknown. Hence, this study was aimed to research the inhibition of MG on S. aureus -induced apoptosis and autophagy in RAW264.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Furthermore, the relative cell viability assay showed that USA300 and XD69 exhibited stronger pathogenicity to MAC-T cells compared with that of other S. aureus strains in vitro. The relative cell viability assay also presented similar results with cytotoxicity assay [63]. These studies indicated that the four virulence factors of S. aureus can destroy the cell membrane [6,8,9,11].…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, the relative cell viability assay showed that USA300 and XD69 exhibited stronger pathogenicity to MAC-T cells compared with that of other S. aureus strains in vitro. The relative cell viability assay also presented similar results with cytotoxicity assay [63]. These studies indicated that the four virulence factors of S. aureus can destroy the cell membrane [6,8,9,11].…”
Section: Discussionsupporting
confidence: 69%
“…An interesting aspect that should be taken into account is that A. theiformis which contains more than 98% of mangiferin and derivatives showed the higher protective effect. Several studies on mangiferin revealed its protective effects on cell survival both in vivo and in vitro , in models involving oxidative stress [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, 122 overlapped genes between WWXDY and S. aureus-related genes mainly belonged to apoptosis-related genes (CASP3, CASP8, CASP1, and SYK), chemokines (MMP2, MMP9), and metabolic genes (Nox4, GLO1). S. aureus infection has been proved to affect cell proliferation, apoptosis, metabolism, as well as secretion of chemokines [20][21][22]. Therefore, WWXDY has a great potential in the treatment of S. aureus infection.…”
Section: Discussionmentioning
confidence: 99%